Pengaruh Latihan dengan Push Bike terhadap Keseimbangan dan Koordinasi Tubuh pada Anak Usia Dini di Club Surabaya Runbike Kids - Ernesto Wardanto; Muhammad Dzul Fikri; Soni Sulistyarto; Heri Wahyudi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
Early childhood motor development, particularly balance and coordination skills, is strongly influenced by the type of physical activities provided. One appropriate form of physical activity is push bike training. A push bike is a pedal-less bicycle that enables children to develop body control, maintain stability, and improve coordination through foot propulsion and balance regulation. This study aimed to examine the effect of push bike training on improving balance and coordination abilities in early childhood at the Surabaya Runbike Kids Club. The research employed a quasi experimental method using a Pretest Posttest Control Group Design. The participants consisted of 10 children aged 5–6 years, divided into an experimental group and a control group, with five children in each group. The research instruments included a straight line walking test to assess balance and a lateral jump test to measure coordination. Data analysis was conducted using the Shapiro Wilk test, Levene’s test, Paired Sample t-Test, and Independent Sample t-Test. The results indicated a significant improvement in the experimental group for both balance and coordination skills. Significant differences were also found between the experimental and control groups in posttest scores for balance and coordination. In conclusion, push bike training is effective in enhancing balance and coordination abilities in early childhood.